Explaining school entry math and reading achievement in Canadian children using the Opportunity-Propensity framework. (February 2019) - Ribner, Andrew; Harvey, Elizabeth; Gervais, Roger; Fitzpatrick, Caroline
Abstract: The Opportunity–Propensity framework predicts that academic success is a function of: (a) Antecedent; (b) Opportunity; and (c) Propensity factors. The aim of the present study was to replicate and expand the O-P framework model with a population-based representative sample of French-Canadian children. The sample consisted of 2120 children followed in the context of the Quebec Longitudinal Study of Child Development (QLSCD). Structural equation models revealed that the O-P framework provided a good fit to the Canadian data and predicted 55 and 51% of the variance in kindergarten math and verbal achievement, respectively. Furthermore, the addition of previously unexamined antecedent (i.e., gestational smoking), opportunity (i.e., home literacy activities), and propensity (i.e., motor skills) predictors contributed significant variance to the model. Similarities and differences between the Canadian findings and those obtained with American samples are discussed in terms of social policy and intervention programs. Highlights: Research with American samples suggests that the O-P framework accounts for variance in school readiness and achievement. In the present study, we attempt to replicate previous findings using a sample of French-Canadian children. Our results suggest that the O-P framework accounts for substantial variance in the math and verbal achievement of Canadian children. Key similarities and differences also appeared in our study and are discussed in the context of policy and intervention.